I would prove this by trying all the possible values of P and Q. There are only Four combinations, T,T, T,F, F,T and F,F for P,Q. Evaluate the left and right sides of each equation for each of the four cases and see if they are equal.
>Can anyone help me prove the following three equivalences: > >(P or Q) and not(P and Q) = (P and notQ) or (Q and notP) > >P <---> Q = (P and Q) or (notP and notQ) > >(P ---> R) and (Q ---> R) = (P or Q) ---> R > >If you could email me with the proofs, I would very much appreciate it. >Thanx in advance. > > -Russell (Russ256@aol.com)